PCDH19-related epilepsy: a rare but recognisable clinical syndrome in females. Issue 4 (28th April 2017) - Lyons, Shane; Marnane, Michael; Reavey, Eleanor; Williams, Nicola; Costello, Daniel
Abstract : Protocadherin 19 (PCDH19)-related epilepsy (OMIM 300088) is a distinctive clinical syndrome limited to females. We describe a 17-year-old girl who presented to a regional epilepsy clinic with a history of recurrent febrile seizures in infancy. Genetic analysis of the PCDH19 gene revealed a novel heterozygous mutation within a highly conserved region of the gene. Patients with PCDH19 mutations present with clusters of seizures associated with fever. While fever-induced seizures are common to children with PCDH19 and SCN1A mutations, there are certain clinical features that distinguish these genetic syndromes from each other. PCDH19 mutation demonstrates an unusual form of transmission such that only heterozygous females develop the phenotype. De novo mutations account for most cases although the inheritance is sometimes familial patterns of inheritance. Hemizygous males are typically unaffected. Identification of the mutation provides patients and their families with an explanation for their clinical presentation, important prognostic information and an opportunity for genetic counselling.